Aplikasi Laundry Nalendra berbasis Android - Rene Matthew Winarto; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
Laundry Service often used by people who have a lot of activity and a lack of time to do housework, specially in the case of washing clothes. Most use the services of a maid. The problem that comes is the consumer who has ordered the items can not know what they are in the process. So if you want to question the status of the items, they will call or SMS. Therefore, the research made by using the application.With applications installed in the gadget on the Android operating system, this application Service can be accessed more practical and very easy to use, as well as other benefits can save time and costs. Application laundry, is a system-based information with mobile devices designed with HTML5 and assisted compilation by Phonegap. While the admin application using PHP and powered by Google Map. Making his system admin using Notepad ++ tools and implemented in the Chrome Browser. While the courier has applications also can see the list between the items and the list of customer orders. This application using HTML and then be converted to apk.As a result of this implementation can generate an application website for admins to update the data item, the consumer receives a request, view transaction details from consumers and financial reports. Meanwhile, the consumer can place an order by courier, see all the details of existing services. Of the courier can do note consumer goods to be washed.